Om alternativ dramaturgi i enaktare författade av kvinnor under det moderna genombrottet - Lyngfelt , Anna (Tidskrift för genusvetenskap, 1997)
In one-act plays written by women at the time of the advance of modernism in Scandinavia, a wish to take an active part in the changing of society is noticeable. Women playwrights discovered that it was possible to make use of t h e female audience's interest in parlour dramatisation a n d epic; by using for instance the tradition of the tableaux vivant's they could appear as new and refreshingly unconventional - but not overtly so - a n d thereby manage to get their plays produced. By this strategy they could take an active part in the ongoing debate on marriage and women's situation in general.